The evaluation of "Safe Motherhood" program on maternal care utilization in rural western China: a difference in difference approach - Liu Xiaoning; Yan Hong; Wang Duolao (BMC, 2010)
Abstract Background Maternal care is an important strategy for protection and promotion of maternal and children's health by reducing maternal mortality and improving the quality of birth. However, the status of maternal care is quite weak in the less developed rural areas in western China. It is found that the maternal mortality rates in some western areas of China were 5.8 times higher than those of their eastern costal counterparts. In order to reduce the maternal mortality rates and to improve maternal care in western rural areas of China, the Chinese Ministry of Health (MOH) and the United Nations Children's Fund (UNICEF) sponsored a program named "Safe Motherhood" in ten western provinces of China from 2001 through 2005. This study mainly aims to evaluate the effects of "Safe Motherhood" program on maternal care utilization. Methods 32 counties were included in both surveys conducted in 2001 and 2005, respectively. Ten counties of which implemented comprehensive community-based intervention were used as intervention groups, while 22 counties were used as control groups. Stratified 3-stage probability-proportion-to-size sampling method was used to select participating women. Two cross-sectional surveys were conducted with questionnaires about the prenatal care utilization in 2001 and 2005, respectively. Difference in difference estimation was used to assess the effect of intervention on the maternal care utilization while controlling for socio-economic characteristics of women. Results After the intervention, the proportion of pregnant women who had their first prenatal visit in the first trimester was increased from 38.9% to 76.1%. The proportion of prenatal visits increased from 82.6% to 98.3%. The proportion of women mobilized to deliver in hospitals increased from 62.7% to 94.5%. Hospital delivery was improved greatly from 31.1% to 87.3%. The maternal mortality rate was lowered by 34.9% from 91.76 to 59.74 per 100,000 live births. The community-based intervention had increased prenatal visits rate by 5.2%, first prenatal visit in first trimester rate by 12.0% and hospital delivery rate by 22.5%, respectively. No effect was found on rate of women being mobilized to hospital delivery compared with that of the control group. Conclusion The intervention program seemed to have improved the prenatal care utilization in rural western China.